2013
DOI: 10.1111/cmi.12137
|View full text |Cite
|
Sign up to set email alerts
|

A key role for lipoic acid synthesis duringPlasmodiumliver stage development

Abstract: SUMMARY The successful navigation of malaria parasites through their life cycle, which alternates between vertebrate hosts and mosquito vectors, requires a complex interplay of metabolite synthesis and salvage pathways. Using the rodent parasite Plasmodium berghei, we have explored the synthesis and scavenging pathways for lipoic acid, a short-chain fatty acid derivative that regulates the activity of α-ketoacid dehydrogenases including pyruvate dehydrogenase. In Plasmodium, lipoic acid is either synthesized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 78 publications
1
39
0
2
Order By: Relevance
“…This view was supported by genetic and biochemical studies in Plasmodium and T. gondii, which demonstrated loss of FASII impacted only PDH lipoylation [45,165], and lipoic acid scavenged from the medium contributed uniquely to lipoylation of mitochondrial enzyme complexes [83,85]. However, in addition to decreasing PDH lipoylation, both the P. falciparum and P. berghei LipB knockouts displayed a lesser but significant reduction in the lipoylation of mitochondrial enzymes [84,164]. These findings challenge the view that apicoplast and mitochondrial lipoic acid metabolism act in strict isolation, and indicate further research is required to fully understand the role of LipB and the lipoic acid synthesis pathway beyond the apicoplast.…”
Section: Octanoyl-acp:protein Transferase (Lipb)mentioning
confidence: 93%
See 3 more Smart Citations
“…This view was supported by genetic and biochemical studies in Plasmodium and T. gondii, which demonstrated loss of FASII impacted only PDH lipoylation [45,165], and lipoic acid scavenged from the medium contributed uniquely to lipoylation of mitochondrial enzyme complexes [83,85]. However, in addition to decreasing PDH lipoylation, both the P. falciparum and P. berghei LipB knockouts displayed a lesser but significant reduction in the lipoylation of mitochondrial enzymes [84,164]. These findings challenge the view that apicoplast and mitochondrial lipoic acid metabolism act in strict isolation, and indicate further research is required to fully understand the role of LipB and the lipoic acid synthesis pathway beyond the apicoplast.…”
Section: Octanoyl-acp:protein Transferase (Lipb)mentioning
confidence: 93%
“…In P. berghei, disruption of LipB had no effect on bloodstage growth, but again led to a substantial decrease in PDH lipoylation [164]. Beyond the bloodstage, loss of PbLipB resulted in defects only in late liver stage development, with knockout sporozoites typically failing to establish a patent infection in mice [164]. As this phenotype mirrored that of the PDH and FASII knockouts in rodent models [97][98][99][100], it indicated the defect most likely resulted from disruption of FASII [164].…”
Section: Octanoyl-acp:protein Transferase (Lipb)mentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, P. berghei liver-stage parasites lacking FabI in C57BL/6 mice or FabB/F in either BALB/c or C57BL/6 mice were severely but incompletely attenuated, resulting in breakthrough infection that developed into normal blood-stage growth (11,14). Furthermore, deletion of P. yoelii genes coding for the apicoplast-targeted pyruvate dehydrogenase complex (PDH) (18), which is essential for the creation of acetyl-coenzyme A (CoA), a precursor of FAS-II, as well as deletion of the gene coding for P. berghei apicoplast-targeted octanoyl transferase (19), which is necessary for the lipoylation of the PDH E2 subunit, led to late liver-stage arrest (19,20). Thus, studies on models of rodent malaria have shown that the deletion of genes involved in all aspects of FAS-II cause growth arrest during liver-stage development.…”
mentioning
confidence: 99%